2019
DOI: 10.1016/j.csbj.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

2D-SAR, Topomer CoMFA and molecular docking studies on avian influenza neuraminidase inhibitors

Abstract: Avian influenza is a serious zoonotic infectious disease with huge negative impacts on local poultry farming, human health and social stability. Therefore, the design of new compounds against avian influenza has been the focus in this field. In this study, computational methods were applied to investigate the compounds with neuraminidase inhibitory activity. First, 2D-SAR model was built to recognize neuraminidase inhibitors (NAIs). As a result, the accuracy of 10 cross-validation and independent tests is 96.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In the current study, we observed sites for leucine zipper in duck TLR3, which is an inherent characteristic for dimerization. Earlier studies have also reported that TLR3 forms a large horseshoe shape that contacts with a neighboring horseshoe, forming a “dimer” of two horseshoes ( Niu et al, 2019 ). As already explained that glycosylation is an important PTM (posttranslational modification site), it acts a glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed sites for leucine zipper in duck TLR3, which is an inherent characteristic for dimerization. Earlier studies have also reported that TLR3 forms a large horseshoe shape that contacts with a neighboring horseshoe, forming a “dimer” of two horseshoes ( Niu et al, 2019 ). As already explained that glycosylation is an important PTM (posttranslational modification site), it acts a glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The Total score is a complex score obtained by docking the receptor and ligand with corresponding parameters using Surflex-Dock procedure. It is generally believed that when the conformation of the ligand and receptor complex is stable, the higher the Total score, the higher the affinity of the receptor and ligand 55 . Total Score > 4.0 indicates certain binding activity, Total Score > 5.0 indicates good binding activity, while Total Score > 7.0 indicates strong binding activity 56 .…”
Section: Methodsmentioning
confidence: 99%